2019
DOI: 10.1002/adfm.201806353
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Functionalized Conductive Nanowire Array Electrode as a Promising Candidate for Bacterial Environment Application

Abstract: Conductive polymer electrodes are widely used for electrical signal detection owing to their unique mechanical, redox, and impedance characteristics. However, the performance of electrodes is compromised due to the interference of adhered bacteria and most of the scientists have not taken the microbial environment into consideration during electrode design. Here, a facile approach to construct antimicrobial peptide (AMP) functionalized polypyrrole nanowire array conductive electrodes (PNW-AMP) is reported. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In recent years, PPy NWs arrays have received attention from researchers and have broad application prospects in the field of supercapacitors and sensors [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Using oxidative polymerization in air, Kim et al [ 78 ] obtained stretched monomeric menisci by pulling on a micropipette containing a Py solution.…”
Section: Types Of Ppy Nanomaterialsmentioning
confidence: 99%
“…In recent years, PPy NWs arrays have received attention from researchers and have broad application prospects in the field of supercapacitors and sensors [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Using oxidative polymerization in air, Kim et al [ 78 ] obtained stretched monomeric menisci by pulling on a micropipette containing a Py solution.…”
Section: Types Of Ppy Nanomaterialsmentioning
confidence: 99%
“…A growing number of studies have demonstrated that certain patterns of electrical stimulation produce cell membrane depolarization and certain prescribed ion movements promote cell proliferation [ [19] , [20] , [21] ]. It also has been found that high intensity electrical stimulation effectively penetrates bacterial walls and destroys bacteria [ 22 , 23 ]. A controlled electrical potential presents the opportunity to integrate antibacterial activity and cell proliferation programmatically via electrical switching.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, a number of membrane-active peptides or amphipathic polymers with weakly ionizable and hydrophobic groups could interact with the hydrophobic interiors of phospholipid bilayers and subsequently assist membrane permeabilization or fusion, such as antimicrobial peptides and cell-penetrating peptides. Universally, it was assumed that the balance of hydrophobicity and cationic charge was an essential ingredient for optimization of antimicrobial activity combined with low toxicity to tissue cells . With a similar point of view, the obtained glycopeptides are designed with an expected balance property that glycopeptides interact with the cell membrane to provide membrane stabilization.…”
Section: Resultsmentioning
confidence: 99%